Determinants of QRIS User Information: The Role of Usage Barriers, Value Barriers, Risk Barriers, Initial Trust, and Perceived Usefulness - Septia S. Dioh; Taqwa Sultan; Irience R. A. Manongga; Maria S. Lou Kelen; Wihelmina Muni; Andrias U. T. Anabuni (Journal of Practical Management Studies, 2026)
This study examines the determinants of QRIS user information by integrating innovation resistance and technology acceptance perspectives within Indonesia’s nationally standardized digital payment system. Using a quantitative explanatory design, data were collected from 105 QRIS users in Kupang City through a structured questionnaire. Multiple linear regression analysis was employed to test the effects of usage barrier, value barrier, risk barrier, initial trust, and perceived usefulness on user information, following validity, reliability, and classical assumption testing. The results show that usage barriers negatively influence QRIS user information, whereas value barriers, risk barriers, initial trust, and perceived usefulness have significant positive effects. Among all predictors, risk barrier emerges as the most dominant determinant, indicating that security and uncertainty perceptions play a critical role in shaping users’ informational engagement. The proposed model explains 65.8% of the variance in user information, demonstrating strong explanatory power. This study adopts a cross-sectional design and focuses on a single geographic context, which may limit generalizability. Future research may employ longitudinal or comparative approaches to capture dynamic and contextual variations. This study advances digital payment and information systems literature by repositioning user information as a central cognitive outcome of user–technology interaction rather than merely an antecedent of adoption, offering an information-centric framework for evaluating the effectiveness of standardized digital payment systems.